2003
DOI: 10.1080/09595230310001613967
|View full text |Cite
|
Sign up to set email alerts
|

Smoking cessation interventions for in‐patients: a selective review with recommendations for hospital‐based health professionals

Abstract: A selective review of the literature was conducted to provide evidence-based recommendations for the clinical management of hospitalized smokers. The Cochrane library, in particular the Cochrane review of 'Interventions for smoking cessation in hospitalised patients', was the basis for the review and was supplemented with other clinical and non-clinical literature where the review did not inform clinicians sufficiently. Evidence was reviewed on issues considered by the authors to be of importance to health pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 45 publications
0
34
0
Order By: Relevance
“…Previous work by the authors describes the need for multicomponent interventions in hospital settings [28]. The current study has found that the annual cost of delivering such interventional components to dependent smokers was approximately £5869, or £154 per incremental patient abstinent at the 3-month follow-up.…”
Section: Discussionmentioning
confidence: 67%
“…Previous work by the authors describes the need for multicomponent interventions in hospital settings [28]. The current study has found that the annual cost of delivering such interventional components to dependent smokers was approximately £5869, or £154 per incremental patient abstinent at the 3-month follow-up.…”
Section: Discussionmentioning
confidence: 67%
“…Post-discharge support, which should be individualized and prolonged, with or without the use of medications, is essential for treatment success. (25) Simply prohibiting smoking in the hospital environment is an insufficient intervention for these patients. At the HUAP, physicians refer all smoking outpatients to experts in smoking cessation, regardless of the nature of the underlying disease.…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that smoking cessation interventions delivered only during the inpatient period do not significantly increase long-term quit rates, because they fail to provide the necessary ongoing support to address the high rate of relapse after discharge (Rigotti, Munafò, Murphy, & Stead, 2002;Warner, Patten, Ames, Offord, & Schroeder, 2004;Wolfenden, Campbell, Walsh, & Wiggers, 2003). Whereas a variety of methods are available to hospitals to provide postdischarge smoking cessation support to smokers, those relying on patient initiation or attendance, such as access to telephone counseling services or referral to group-based treatment, fail to reach the majority of smokers (Ockene et al, 1992;Winickoff, Buckley, Palfrey, Perrin, & Rigotti, 2003;Winickoff, Hillis, Palfrey, Perrin, & Rigotti, 2003).…”
Section: Introductionmentioning
confidence: 99%